COVID-19 in India: Disease Burden, Managing the Second Wave and Innovations - Nirupam Bajpai; Manisha Wadhwa (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2021)
The second wave of COVID-19 caused havoc across India. It was twice as severe as the first one. More than 400,000 COVID-19 cases per day were being reported. The worst affected states were Maharashtra, Kerala, Karnataka, Tamil Nadu, Delhi and Andhra Pradesh. The spike in cases was largely assumed to be the result of leniency in COVID-19 appropriate behaviour, such as people were not wearing masks, resumption of economic activity, gathering in large numbers e.g. in marriages, political meetings, rallies, IPL matches, religious gatherings like Kumbh Mela etc. 67 percent of India's population above the age of six years has been exposed to COVID-19 according to a national serological survey conducted by ICMR, the findings of which were revealed on July 20, 2021. The survey was conducted during June and July across 70 districts of 21 states. These are the very same districts where three earlier rounds of sero surveys were conducted during May-June 2020; August-September 2020 and December-January 2020/21. On January 16th 2021, India launched the world's largest vaccination drive and as of July 15, more than 391,340,491 vaccine doses had been administered across the country. The vaccine has been administered in a phased manner with the initial focus being on priority groups like health workers, frontline workers like the police workforce, municipal workers, defence personnel etc., people above 60 years of age and those between 45-60 years with co-morbidities. From May 1, 2021, people between age group 18-45 were also eligible for vaccination. But, until a substantial proportion of the population is vaccinated, precautionary measures like wearing masks, sanitization, regular hand washing and physical distancing must remain the mainstay. Inter-departmental coordination has been the cornerstone in dealing with COVID-19 situation in India. Various departments such as Health, Tourism, Defence, Information and Communication Technology (ICT), Finance etc. took various initiatives in collaboration with other departments to deal with the pandemic. Challenges posed by COVID-19 also sparked a wave of innovations across sectors in India. A host of new interventions were implemented by various departments, such as health, agriculture, education, police, railways etc. This document is based on secondary data collected from government documents and websites, news reporting, media interviews, newspaper articles, various national and international journals and private websites. The present paper discusses current scenario of COVID-19 in India, COVID-19 vaccination drive, innovative approaches to address vaccine hesitancy in India, inter-departmental coordination and innovation across sectors in dealing with COVID-19 situation. We also put forward recommendations to deal with the surge in COVID-19 cases in future and to scale up innovations and undertake research studies to identify gaps and address challenges.
Keywords: 330